Efek Ekstrak Etanol Bawang Lanang (Aliium sativum L.) terhadap Paralisis dan Kematian Cacing Dewasa Ascaris suum, Goeze - M. Zainul Fikri; Reza Hakim; Dini Sri Damayanti (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: Single Garlic (Allium satuvum L.) can be an alternative cure for the Ascariasis disease because it has compound anti-helmintik like saponin, allicin, and flavonoid that can kill a worm contained in the human body.Method: This research uses the in vitro experimental laboratory. In the sample collection Ascaris suum , goeze used method of random purposive sampling. Ascaris suum , goeze roundworm used in this study amounted to 28 tail included in 7 groups tube which each canister contains 4 worms. 7 groups tube consist of the negative control group (NaCl 0.9 %), 5 group consist single garlic ethanol extract (0.5 % , 1 % , 2 % , 4 % , 8 % ) , and positive control group (pirantel pamoat 5 mg / ml).Result: The results obtained in the linear regression show significant impact (P>0,05) with the required PC50 0,81% to make the paralysis 50% of the total number of worms and it takes concentration Single Garlic extract LC50 2,09% to make the death of 50% of the total number of worms.Conclusion: Extract ethanol of Single Garlic is having an effect on anti-helmintik Ascaris suum, Goeze roundworms.Key Word: Single Garlic Extract, PC50 Paralysis, LC50 Death, Ascaris suum Goeze Adult Worm